2016
DOI: 10.1542/peds.2016-1357
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Stimulation and Early Child Development in Low- and Middle-Income Countries

Abstract: BACKGROUND AND OBJECTIVE: Few studies have examined the relationship between paternal stimulation and children's growth and development, particularly in low-and middle-income countries (LMICs). This study aimed to estimate the prevalence of paternal stimulation and to assess whether paternal stimulation was associated with early child growth and development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
109
4
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(129 citation statements)
references
References 45 publications
13
109
4
3
Order By: Relevance
“…These components were as follows: availability of (homemade or purchased) toys, dolls, and books (verified by field enumerator); interactive activities with the mother such as reading together, telling stories, singing together, naming objects, and playing (parent report); and child supervision (number of days per week that the child was left alone or under the supervision of another child, parent report; Kariger et al, ). Responses to these items were scored using the method adapted from (Jeong, McCoy, Yousafzai, Salhi, & Fink, ); a composite score incorporating these three categories was calculated. Scores were normally distributed (median 4, range −2 to 11) and treated as a continuous variable in models.…”
Section: Methodsmentioning
confidence: 99%
“…These components were as follows: availability of (homemade or purchased) toys, dolls, and books (verified by field enumerator); interactive activities with the mother such as reading together, telling stories, singing together, naming objects, and playing (parent report); and child supervision (number of days per week that the child was left alone or under the supervision of another child, parent report; Kariger et al, ). Responses to these items were scored using the method adapted from (Jeong, McCoy, Yousafzai, Salhi, & Fink, ); a composite score incorporating these three categories was calculated. Scores were normally distributed (median 4, range −2 to 11) and treated as a continuous variable in models.…”
Section: Methodsmentioning
confidence: 99%
“…For example, application and call logs have also been used to determine communication (44). In case of mother-child interaction, we suggest using additional observation tools such as HOME (27,45,46) and OMCI (47)(48)(49) which have been used in multi-cultural settings to assess mother and child's social environment, interactions and support. Finally, additional methods of passive data collection, such as Bluetooth beacons attached to child's clothing can help determine the time mother and child spend together (19,29).…”
Section: Discussionmentioning
confidence: 99%
“…With evidence pointing solidly to the benefits of paternal involvement for early child development in high-income countries, in this issue of Pediatrics, Jeong et al set out to describe the prevalence of paternal stimulation in 38 low-and middle-income countries (LMIC) among children <5 years old and showed that it relates positively to the Early Childhood Development Index, which measures early child development in literacy/numeracy, physical, social-emotional, and learning contexts. 2 The effect sizes of high paternal stimulation were similar in magnitude to those of mother completing primary school and an increase in wealth that delivers the family out of the poorest quintile. Furthermore, the associations between paternal stimulation and Early Childhood Development Index were more pronounced for children receiving less stimulation from others (mother or education professionals).…”
mentioning
confidence: 81%
“…In fact, it appears that a significant portion of the variation in father engagement at the country level can be explained by poverty indices. For example, the correlation between the percentage of unengaged fathers (taken from Appendix C) 2 Opinions expressed in these commentaries are those of the author and not necessarily those of the American Academy of Pediatrics or its Committees.…”
mentioning
confidence: 99%